The Effect of A Training Program For Developing Some Physical Abilities of Participants in Female Training Institutes - Fadl, Abbaas; Raad, Meena (Journal of Physical Education, 2018)
The Effect of A Training Program For Developing Some Physical Abilities of Participants in Female Training Institutes The researchers aimed at designing a training program for developing some physical abilities of female participants in training institutes courses and identifying the effect of this training program on the development of some physical abilities of female participants in training institutes courses. The researcher used the experimental method. The subjects were (36) female participants in the training institute 2017 – 2018 aged 20 – 25 years old. The subject was divided into two equal groups 15 each and six formed the pilot study. The researchers concluded that the training program affect the development of physical abilities in participants and the training program affected the general performance as well because it is designed to improve many variables one of them is physical variables. Finally the researchers recommended using the training program for developing physical abilities of participants in training institutes as well as making similar studies to evaluate programs designed by the ministry in all training courses for women training institutes.